The Influence of the Padlet-Assisted Discovery Learning Model on Students' Digital Literacy Skills in the Respiratory System - Siti Sobariyah, Nuni; Romy Faisal Musthofa; Dani Ramdani (Universitas Islam Negeri Walisongo Semarang, 2025)
The advancement of information technology requires students to have good digital literacy skills to be able to access, evaluate, and utilize information effectively in the learning process. The purpose of this study was to determine the effect of the Padlet-assisted discovery learning model on students' digital literacy skills on the respiratory system material in grade XI of SMAN 1 Cikatomas. The research method used was a quasi-experimental with a posttest-only control group design. The study population included all grade XI with samples determined through purposive sampling, consisting of one experimental class and one control class. The research instrument was a validated digital literacy questionnaire. Data analysis was carried out using the One Way ANOVA test. The results showed a significant difference between the experimental class and the control class in digital literacy skills. Thus, it can be concluded that the application of the Padlet-assisted discovery learning model has a positive effect on students' digital literacy skills on the respiratory system material.